The Watson's go to Birmingham 1963 - Curtis, Christopher Paul (New York : Bantam Doubleday, 1999)
The ordinary interaction and everyday routines of the Watsons, an African American family living in Flint, Michigan are drastically changed after they go to visit Grandma in Alabama in the summer of 1963
Keywords: Fiction